Interaction of subgrade resistance and dimensions of asphalt pavement surface cracks on propagation of secondary distresses - Khabiri, Mohammad Mehdi; Saberian, Mohammad; rahgozar, Mohammad Ali (International Journal of Integrated Engineering, 2017)
Reactions created in road construction and secondary distresses made in pavement are dependent on dimensions and geometry of cracks, resistance of subgrade and existing pavement layers. Thus, this essay assessed the effect of changes in crack’s geometry and also the amount of subgrade resistance on settlement in the cracking place. Since pavement layers thickness has a drastic effect on the resistance of the layers, cracks propagation and secondary distresses, in this essay, different types of strong, semi-strong, and weak pavements have been considered according to combination of different thicknesses for the pavement layers which are respectively wearing layer with the thickness of 5, 10, 20 centimeters, base course with thickness of 10, 20, 40 centimeters and sub base with thickness of 15, 30 and 60 centimeter. Also, as pavement can be constructed in grounds with different resistance and so subgrade resistance has an important role in pavement settlement  and distresses, in this essay, subgrade have been studied in three types of dense sand (strong soil), fine sand (semi-strong soil), and soft clay (weak soil) with different geotechnical properties. So, for preventing the mentioned problems, layers’ behavioral properties are considered as Mohr Coulomb-plastic and by three-dimensional modeling with finite element software of ABAQUS, we studied the degree of subgrade and cracked pavement surface settlement with different forms of cracking in different types of pavement and subgrade situations, like different thickness and behavioral properties. Then, to check results and validating software, by field observation, level of settlement in different cracking places was gathered and compared to the numerical results of the software. Results of finite element software show that by 25% increase in crack opening, the level of settlement of the surface layer and  the surface of subgrade would increase by 49% and 38% respectively. Also the level of the surface and subgrade settlement would rise by increase in crack depth; and the measurements for 25% increase in crack depth are 16% for surface and 13% for subgrade. In addition, by increasing in the width of crack in soils with different resistance, width line slope of crack-settlement in weak soil would be about triple compared to strong soil, and by increase in depth of crack in soils with different resistance, depth line slope of crack-settlement in weak soil would be about twice compared to strong soil. By the use of probabilistic analysis, It was determined that in 95% confidence interval, cracking on deformation of surface and subgrade, is significantly under the influence of subgrade type and as the subgrade weakens, the amount of deformation will increase more.